(3cJGH GdfGUQi aj GdHjWQI (B( (3cGed GdUfGYJjf (B)s - (3YHO Gddg Hf GdHOQ GdHjWGQ GdeUQj, GHf GdefPQ, CHh HcQ , J (B741 (3g` s ((3GHh HcQ Hf GdHOQ GdHjWGQ s)
(3ChdgG (B:s
(3hHYO abO GJe Gddg JYGdi hLOO SYO ehdGfG GdSdWGf TGgQeGf SjO edhc GdReGf eGdc QbGH GdGee s
(3BNQgG (B:s
(3hOaY GdeVGQO hdcfgG ddeJCNQ Hf GdHjGWQI hGdUfGY s
(3fSNI NRGFfjI HQSe Gdedc GdfGUQ eMeO Hf THc hjMJhi Ydi YTQI ebGdGJs
(3hHBNQ (B3 (3UaMGJ ai GdaQhSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B76s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B- (3JQcjG (B(1956) s
Keywords: (3GdWHs